Contrasting apatite geochemistry between ore-bearing and ore-barren intrusions of the giant Kalmakyr gold-rich porphyry Cu deposit, Tien Shan, Uzbekistan - Liu, Yangtao; Zhao, Xiaobo; Xue, Chunji; Nurtaev, Bakhtiar; Chen, Jing (Frontiers in Earth Science, 2023)
The Kalmakyr deposit in Uzbekistan is one of the world’s largest gold-rich porphyry Cu deposits, and mineralization was proposed to be closely associated with emplacement of the latest intrusive phases, i.e., granodiorite porphyry. However, which features of this ore-bearing intrusion are crucial for the enormous metal enrichment and how they correlate to magmatic fertility are still not fully understood. In this study, we address these questions by comparing petrological, and in-situ major and trace element geochemistry of apatite for the ore-bearing and ore-barren intrusions. Magmatic apatite from the ore-bearing granodiorite porphyry has higher Eu/Eu* (0.50-0.58), Sr/Y (1.09-1.64), and La/Yb (36.19-53.42) ratios compared with the ore-barren quartz porphyry (0.01-0.02, 0.02-0.03, 2.01-3.75, respectively) and monzonite (0.20-0.11, 0.36-1.12, 19.71-56.32, respectively). Moreover, the ore-bearing granodioritic magma has higher S (average of 111 ppm) and Cl (average of 8602 ppm) contents than magmas of quartz porphyry (S contents average of 9 ppm; Cl contents average of 2652 ppm) and monzonite (S contents average of 9 ppm; Cl contents average of 8483 ppm). These features collectively suggest that the ore-bearing granodiorite porphyry has relatively high oxygen fugacity, H2O, Cl, and S contents compared to those from the ore-barren intrusions. By comparing our data with the published dataset from porphyry Cu-Mo and Mo-only deposits in the world, we suggest that high Cl content and low F/Cl ratio in magmatic apatite might be an important indicator for prospecting of gold-rich porphyry Cu deposits.